Case Report: Successful treatment of spondyloenchondrodysplasia with immune dysregulation using tofacitinib and ruxolitinib: a report of two pediatric cases - Liu, Chengzhu; Xie, Zhiwei; Wang, Min; Chu, Jinhua; Yang, Linhai; Zhang, Kunlong; Huang, Lingling; Tu, Songji; Cai, Huaju; Wu, Zhengyu; Wang, Liyuan; Wang, Ningling (Frontiers in Pharmacology, 2025)
Spondyloenchondrodysplasia with immune dysregulation (SPENCDI) is autosomal recessive hereditary disease caused by tartrate resistant acid phosphatase 5 (ACP5) mutations. The symptoms mainly involve the bone, immune system and nervous system, and the typical manifestations are short stature, abnormal development of long diaphyseal epiphysis, flat vertebra, and prone to various autoimmune diseases. Some children have muscle spasm, mild mental retardation, intracranial calcification and other neurological manifestations. Here we reported two cases of SPENCDI caused by a new mutation in ACP5. The clinical manifestations were autoimmune hemolytic anemia, immune thrombocytopenia, abnormal bone development, intracranial calcification, short stature, and growth retardation. The patients were girls and diagnosed with SPENCDI by genetic test.